The African neopatrimonial state as a global prototype - (:unkn) unknown (My University, 2011)
The concept of neopatrimonial rule was first applied to Africa in 1978, when Jean-François Médard undertook to account for the Cameroonian state‟s lack of institutionalization and "underdevelopment". The lack of distinction between office and officeholder, Médard went on, is masked behind discourses, juridical norms and institutions that nourish the illusion of a legal-bureaucratic logic. In the absence of a legitimizing ideology, the ruler owes his ability to remain in power to his capacity for transforming his monopolistic control over the state into a source of opportunities for family, friends and clients. Neopatrimonialism in Africa is still classically viewed as the outcome of confusion between office and officeholder within a state endowed, at least formally, with modern institutions and bureaucratic procedures. The introduction of "neo" as a prefix, means that neopatrimonialism is freed from the historical configurations to which patrimonialism had been associated by Weber. The display of legal-bureaucratic norms and structures coexists with relations of authority based on interpersonal rather than impersonal interactions. This coexistence of patrimonialism with legal-bureaucratic elements, begs the key question of the forms of interaction and their outcomes. Indeed, neopatrimonialism infers a "dualistic situation, in which the state is characterized by patrimonialisation, as well as by bureaucratization". Such dualism translates into a wide array of empirical situations. What is ultimately at stake, however, is the state's capacity (or lack thereof) to produce 'public policies: political systems where patrimonial practices tend to be regulated and capped should be distinguished from those where the patrimonialisation of the state has become all-encompassing, with the consequent loss of any sense of public space or public policy.
Keywords: African Research